COMPUTATIONAL MODELLING IN ELEMENTARY MATHEMATICS TEACHER EDUCATION - Gadanidis, Gearge; Hughes, Janette M.; Namukasa, Immaculate; Scucuglia, Ricarda [UNESP] (My University, 2019)
There is growing momentum in education to engage Grades K-12 students with computational tools. At the same time, there is a widening gap between what students experience in classrooms (where the predominant focus is on learning to code as an end itself) and the authentic computational modelling practices of scientists and professionals to solve real-world problems and build knowledge -to learn - through computational “conversation” and “interaction” with their field (Barba, 2014) “with and across a variety of representational technologies” (Wilkerson-Jerde, Gravel, and Macrander, 2015). In this chapter we discuss how our classroom-based research has informed our inclusion and research of computational modelling in elementary mathematics teacher education, and we share examples of the five different modes of computational modelling we integrate in our elementary mathematics teacher education program: unplugged coding, coding simulations, Scratch coding, Python coding, and coding environments we create to model specific math topics and concepts.